2020
DOI: 10.1093/ejcts/ezaa039
|View full text |Cite
|
Sign up to set email alerts
|

Preclosing of the femoral artery allows total percutaneous venoarterial extracorporeal membrane oxygenation and prevents groin wound infection after lung transplantation

Abstract: OBJECTIVES In lung transplantation (LT), femoral venoarterial extracorporeal membrane oxygenation (VA-ECMO) usually requires an open approach that may be associated with severe groin wound infection. In endovascular aortic procedures, preclosing of the femoral artery (PFA) with vascular closure devices allows the percutaneous insertion and withdrawal of large-bore cannulae. We sought to evaluate whether this innovative technique could be applied in the specific setting of LT to achieve total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Cannulation wound complications are serious adverse outcomes that are associated with longer hospital stay, greater cost, and greater mortality, especially after heart transplantation due to immunosuppression, drug-induced diabetes, and preoperative low output status. 12 , 13 , 14 , 15 , 16 , 17 , 18 Salna and colleagues 15 reported that a cutdown procedure is a risk factor for developing FA wound complications in patients undergoing heart transplant. In the present study, arterial de-cannulation was performed by a cutdown technique, as we believed it would result in fewer vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Cannulation wound complications are serious adverse outcomes that are associated with longer hospital stay, greater cost, and greater mortality, especially after heart transplantation due to immunosuppression, drug-induced diabetes, and preoperative low output status. 12 , 13 , 14 , 15 , 16 , 17 , 18 Salna and colleagues 15 reported that a cutdown procedure is a risk factor for developing FA wound complications in patients undergoing heart transplant. In the present study, arterial de-cannulation was performed by a cutdown technique, as we believed it would result in fewer vascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, with the increase of structural heart disease interventions and large bore vascular accesses, this technique is now mastered by most of the interventional cardiologists. Preclosing has been studied by Pellenc et al in ECMO implanted prior to lung transplantation, with a dramatic reduction in the rate of groin wound infection as compared to open surgery [ 12 ]. The patients included in this study were however different from ours.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding removal, surgical femoral cutdown is considered as standard practice but frequently associated with severe complications such as hemorrhage, delayed wound healing and infections [ 11 , 12 ]. Other techniques such as manual compression or post-closing using closing devices have been described but none of these are ideal [ 10 , 11 , 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…4,6,7 Further, in a previous study of the use of the preclosure technique in elective peripheral VA-ECMO before lung transplantation, similarly low rates of site infections were noted. 14 Historically, it has been typical to perform surgical vascular repair with exposure and repair of the common femoral artery at the time of decannulation from VA-ECMO. This open surgical procedure was associated with the risks of an open operation, related decreased patient mobility following its completion, and potential for seroma formation.…”
Section: Discussionmentioning
confidence: 99%